Effect of plant spacing on pigeonpea grain yield in Northern Uganda - Kumakech, Alfred; Opio, Tonny; Turyagyenda, Frank Laban (Brazilian Journal of Science, 2024)
The aim of crop production is to achieve the highest possible yield per unit area. One way of increasing productivity per unit area is through plant spacing optimization. The effect of plant spacing (90 cm x 60 cm, 150 cm x 120 cm and 150 cm x 180 cm) on yield of three pigeonpea genotypes (KAT 60/8, ICEAP 00540 and ICEAP 00554) was investigated on-station in a small-plot field experiments in 2018. Significant differences were recorded in grain yield of all the three genotypes. The highest yield for all the three genotypes was recorded for row spacing of 90 cm and inter plant spacing of 60 cm, and the lowest for row spacing of 150 cm and inter plant spacing of 180 cm. Plant spacing effect on other yield parameters (number of pods per plant and 100 seed weight) were not significant. Similar effects were recorded for plant growth parameters (plant height and number of primary branches). Thus, it can be concluded that row spacing of 90 cm and interplant spacing of 60cm is appropriate for pigeonpea grain production in Uganda.